2020
DOI: 10.3892/etm.2020.9188
|View full text |Cite
|
Sign up to set email alerts
|

<em>In&nbsp;silico</em> prediction and validation of potential therapeutic genes in pancreatic &beta;‑cells associated with type 2 diabetes

Abstract: Diabetes mellitus is becoming a major health burden worldwide. Pancreatic β-cell death is a characteristic of type 2 diabetes (T2D), but the underlying mechanisms of pancreatic β-cell death remain unknown. Therefore, the aim of the present study was to identify potential targets in the pancreatic islet of T2D. The GSE20966 dataset was obtained from the Gene Expression Omnibus (GEO) database, and differentially expressed genes (DEGs) were identified by using the GEO2R tool. The Gene Ontology terms and Kyoto Enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…Diabetes is responsible for 6.8 percent of worldwide mortality in the 20-79 age range and is a primary reason for decreased life expectancy [5,6]. About 10% of diabetic patients have type 1 diabetes (T1D), which is char-acterized by an uncontrolled and destructive immune response to pancreatic beta cells [7,8], whereas the remaining DM patients have type 2 diabetes (T2D), whose main risk factors include overweight, insufficient physical activity, and smoking [9,10]. Numerous clinical studies have shown that lifestyle modifications may successfully prevent the progression of T2D.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes is responsible for 6.8 percent of worldwide mortality in the 20-79 age range and is a primary reason for decreased life expectancy [5,6]. About 10% of diabetic patients have type 1 diabetes (T1D), which is char-acterized by an uncontrolled and destructive immune response to pancreatic beta cells [7,8], whereas the remaining DM patients have type 2 diabetes (T2D), whose main risk factors include overweight, insufficient physical activity, and smoking [9,10]. Numerous clinical studies have shown that lifestyle modifications may successfully prevent the progression of T2D.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of b-cells by HGF increases the phosphorylation of IRS2, AKT and ERK (138). This increase is the response of MET activation by HGF, which induce the formation of a MET-Insulin receptor complex responsible of an increase in insulin signal (136,138,139).…”
Section: Hepatocyte Growth Factormentioning
confidence: 99%